2018
DOI: 10.5830/cvja-2017-030
|View full text |Cite
|
Sign up to set email alerts
|

Effects of age on systemic inflammatory response syndrome and results of coronary bypass surgery

Abstract: SummaryBackgroundCoronary artery bypass (CAB) surgery triggerssystemic inflammatory response syndrome (SIRS) via severalmechanisms. Moreover, age is directly correlated with SIRS.We evaluated the effect of age on SIRS and postoperativeoutcome after CAB surgery.MethodsWe retrospectively reviewed the records of 229 patients who had undergone CAB surgery. The patients were divided into three groups according to age: group 1, < 40 years (n = 61); group 2, 40–75 years (n = 83); and group 3, > 75 years old (n = 85).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…To the Editor: Shroyer and colleagues [1] compared the results of off-pump and on-pump coronary surgery with diabetic patients, of which we read with interest. The systemic inflammatory response, which is a natural result of on-pump coronary artery bypass surgery, may undoubtedly affect the operation results [2]. We agree with Shroyer and associates that it is better to use on-pump surgery because of the comfort and the higher rate of complete revascularization of this technique.…”
Section: Factors Affecting Postoperative Mortality In Coronary Bypass Surgerysupporting
confidence: 70%
See 2 more Smart Citations
“…To the Editor: Shroyer and colleagues [1] compared the results of off-pump and on-pump coronary surgery with diabetic patients, of which we read with interest. The systemic inflammatory response, which is a natural result of on-pump coronary artery bypass surgery, may undoubtedly affect the operation results [2]. We agree with Shroyer and associates that it is better to use on-pump surgery because of the comfort and the higher rate of complete revascularization of this technique.…”
Section: Factors Affecting Postoperative Mortality In Coronary Bypass Surgerysupporting
confidence: 70%
“…These supplementary analysis results suggest that the ROOBY-FS (Randomized On/Off Bypass -Follow-up Study) findings-that off pump had an adverse impact on 5-year death in patients with MTD-appear robust [2]. These results may be…”
Section: Replymentioning
confidence: 79%
See 1 more Smart Citation
“…In a study by Rostami et al, a fever was reported in 29.9% of CABG patients ( 25 ). A fever immediately after cardiopulmonary bypass surgery is associated with cognitive impairment, after CABG ( 26 , 27 ), which potentially could be considered as a sepsis sign itself.…”
Section: Discussionmentioning
confidence: 99%
“…Activated platelets in turn release neutrophils activators such as Il-6 and Il-8 [91]. OPCAB technique allows to limit inflammatory activation [92] which occurs in 70-90% patients undergoing conventional coronary artery bypass grafting with cardiopulmonary bypass (on-pump) [93]. Systemic inflammatory reactions secondary to on-pump procedures represent the significant risk factor for postoperative multiple organ dysfunction (MOD) [94].…”
Section: Inflammatory Activation Technique-related In Perioperative P...mentioning
confidence: 99%